Analisis Faktor Penentu Minat Nasabah Terhadap Penggunaan Aplikasi Mobile Banking Syariah: Integrasi Model TAM - Mira Puspitasari; Rachma Indrarini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Innovations in digital applications such as Islamic mobile banking offer convenience and efficiency in conducting financial transactions. However, the presence of this technology has also given rise to various risk perceptions among the public. Therefore, it is necessary to understand the factors that influence customers’ intention to use Islamic mobile banking applications. This study aims to analyze the impact of several variables, namely perceived ease of use, perceived benefits, social and financial services, and perceived risk on intention to use Islamic mobile banking applications. Quantitative methods were used as the approach in this study. Primary data were collected from 264 respondents selected through purposive sampling using a questionnaire. To analyze the data, the Structural Equation Modeling Partial Least Squares (SEM-PLS) method was used. The results showed that perceived ease of use, perceived benefits, and social and financial services had a positive and significant impact on intention to use Islamic mobile banking application. However, unlike other variables, perceived risk was found to have no significant influence on intention to use the application.